(untitled) (Third Sector Social Economic Review, 2018)
The task of promotion is one of the most important elements of the business life for employees working in public administration and public organizations. Just as in the private sector, public sector employees also want to be promoted in their duties, to have authority and powery, and thus to increase their wages. There are regulations of promotion in the public sector also to meet both these expectations of its employees and to meet the needs for managers in line with the needs of the sector. In other words, the task of promotion is shaped around a system that is prescribed by these legislation. What justice perception which this system has formed in the eye of employees is like has a great importance for the sector and its employees. In this study, it was tried to show whether there is a meaningful difference between the perceptions of justice pertaining to the promotion system on the axis of the working hours of the workers in the public health sector in the Bartın province and it was evaluated whether the total duration of the employees was effective in the justice perceptions of the promotion system. A questionnaire of perception of promotion formed by ourselves was applied to 212 public employees working in the Bartın Provincial Health Directorate, Bartın Public Hospitals Association and Bartın Public Health Directorate, which constitute the Public Health Organization of Bartın province to create a sample. As a result of the surveys carried out and analyzes of questionnaire, the perceptions of the justice of public employees working in the Bartın Public Health Organization on the current task promotion system were evaluated on the basis of hypotheses. In this context, it has been concluded that public health workers with a total of 1-5 and 6-10 years working period have a stronger perception that the promotion system in the current position is unfair and has unfair consequences compared to the age groups with relatively different total service years. Besides, according to the results of the research, it is noteworthy that the perceptions of justice regarding the promotion system in the public health sector in the Bartın province universe, in all working age groups are negatively affected.